Treatment of the Developmental Dysplasia of the Hip with an Abduction Brace in Children up to 6 Months Old - Raphaël Wahlen; Pierre-Yves Zambelli (Advances in Orthopedics)
Introduction. Use of Pavlik harness for the treatment of DDH can be complicated for parents. Any misuse or failure in the adjustments may lead to significant complications. An abduction brace was introduced in our institution, as it was thought to be easier to use. Aim. We assess the results for the treatment of DDH using our abduction brace in children of 0–6 months old and compare these results with data on treatments using the Pavlik harness. Method. Retrospective analysis of patients with DDH from 0 to 6 months old at diagnosis, performed from 2004 to 2009. Outcomes were rates of reduction of the hip and avascular necrosis of the femoral head (AVN). Follow-up was at one year and up to 4 years old. Results. Hip reduction was successful in 28 of 33 patients (85%), with no AVN. Conclusion. Our results in terms of hip reduction rate and AVN rate are similar to those found in literature assessing Pavlik harness use, with a simpler and comfortable treatment procedure.